(untitled) (Plant Tissue Culture and Biotechnology, 2023)
An experiment was conducted to develop a suitable in vitro plant regeneration technique for Rosa hybrida L. cv. ‘Double Delight’ using nodal segments and leaf tissues as explants through direct and indirect organogenesis. Aseptic explants were inoculated onto gelled MS medium contained various strengths of plant growth regulators alone and in combinations for callus and direct shoot induction. MS medium containing 2.0 mg/l BAP was found to be the most effective for direct shoot induction from nodal explants (87.5%) as it produced the maximum number of shoots per explant. The highest callus induction frequency was found to be 80% in leaf tissue, 72% in nodal segments and 96% in leaf and intermodal segments of in vitro raised plantlets in MS medium containing 2.5 mg/l 2, 4-D. The best percentage of indirect shoot organogenesis (93.33%) with maximum number and length of shoot were found when the different explant-derived callus was transferred in 3.0 mg/l BAP supplemented medium. The direct and indirectly induced shoots were multiplied on MS medium containing 3.0 mg/l BAP, where the average number and length of shoots per culture were 7.20 ± 0.80 and 5.22 ± 0.47 cm, respectively. Maximum rooting (80%) was observed in ½-strength of gelled MS medium containing 15.0 g/l sucrose with 1.0 mg/l IBA. Plantlets with the proper root system were then placed in a polybag with a 1:1:1 ratio of sand, garden soil, and compost, and they had a survival rate of about 76%. Plant Tissue Cult. & Biotech. 33(1): 25-36, 2023 (June)